Prophetic Ecopedagogy in Social Studies Learning: Integration of Islamic Values and SDGs Literacy to Strengthen Ecological Intelligence - Nur Fauzi; Raras Gistha Rosardi; Sudrajat Sudrajat; Erika Putri (Universitas Sebelas Maret, 2026)
The knowledge–action gap remains a fundamental challenge in environmental education in Indonesia, as students’ ecological literacy does not consistently translate into concrete pro-environmental behavior. This study aims to examine the integration of Islamic values and Sustainable Development Goals (SDGs) literacy within Social Studies learning through a Prophetic Ecopedagogy approach to strengthen students’ ecological intelligence. A qualitative case study design was employed at SMP Muhammadiyah 3 Yogyakarta. Data were collected through participant observation, in-depth interviews, and document analysis, and were analyzed using the interactive model of Miles, Huberman, dan Saldaña. The findings reveal three main outcomes. First, the Social Studies curriculum shifted from a predominantly hidden curriculum to an explicit curriculum through the formal integration of SDGs targets into lesson planning. Second, the instructional process reflects three pillars of Prophetic Ecopedagogy: Transcendence (environmental stewardship as a theological mandate), Humanization (the climate crisis framed as a humanitarian issue), and Liberation (freedom from consumerist culture through the Zero Waste movement). Third, this approach effectively fosters students’ ecological intelligence, particularly in systemic thinking and digital environmental advocacy. However, behavioral gaps persist in abstract energy conservation practices, in contrast to strong compliance in tangible waste management activities.